HUBUNGAN ANTARA CITRA TUBUH DENGAN PERILAKU MAKAN PADA REMAJA PUTRI - Ni Made Candra Yundarini (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2015)
Physical changes in adolescence are fast, especially in female adolescents, so that they do diet and fall on eating behavior disorder as an effect. This study aims to determine relation between body image and eating behavior on female adolescents in SMA Dwijendra Denpasar. This is a descriptive correlational study with cross sectional approach. Samples consisted of 140 female adolescents that were selected by simple random sampling technique. Data collection was done by filling MBSRQ-AS questionnaire and EAT-26 questionnaire in which both were modified. Study’s results show that most of the participants with negative body image have high risk of eating behavior disorder as much as 26 people (18,5%), while most participants with positive body image have moderate risk of eating behavior disorder as much as 93 people (66,43%). Based on kendall-tau test’s results, it is found that p value of 0,000 (p<0,05) and z count (10,56) > z table (1,96), so that null hypothesis is rejected, which means that there is a relation between body image and eating behavior on female adolescents in SMA Dwijendra Denpasar. Female adolescents need to have positive body image and good eating behavior so that their growth and development won’t be hampered.